2021
DOI: 10.1111/tid.13714
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors, and association of antifungal prophylaxis on early invasive fungal infection in heart transplant recipients

Abstract: Invasive fungal infection following heart transplantation is associated with acute rejection and renal replacement therapy. Antifungal prophylaxis appears to be protective (HR 0.32, 95% CI 0.11-0.96).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Fortunately, regarding viral infections, a large contemporary cohort study on heart transplant recipients demonstrated that cytomegalovirus infection was not associated with cardiac allograft rejection [68]. However, a retrospective cohort study from 2000 to 2009 on 966 patients who underwent heart transplantation depicted that renal replacement therapy and allograft rejection were related to invasive fungal and mold infections [69].…”
Section: Deep Sternal Wound Infection and Other Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, regarding viral infections, a large contemporary cohort study on heart transplant recipients demonstrated that cytomegalovirus infection was not associated with cardiac allograft rejection [68]. However, a retrospective cohort study from 2000 to 2009 on 966 patients who underwent heart transplantation depicted that renal replacement therapy and allograft rejection were related to invasive fungal and mold infections [69].…”
Section: Deep Sternal Wound Infection and Other Infectionsmentioning
confidence: 99%
“…Previous studies have suggested hemodynamically irrelevant pericardial effusion, which could be observed during common echocardiography, is associated with increased mortality in patients as a valuable predictor of adverse outcomes in patients with heart failure [91]. Interestingly, by assessment of 152 patients who underwent heart transplantation from 1989 to 2012, Stämpfli et al revealed that pericardial effusion irrelevant to surgery in heart transplantation recipients could predict adverse outcomes as this early complication able reduction in bacterial, viral, fungal, and Nocardia post-transplantation infectious episodes [62,69,71]. In spite of these effective treatment methods regarding multidrug-resistant and extensively drug-resistant bacterial infections that pivotally threaten one-year survival, the crucial need for further studies appeared to be extremely necessary [63].…”
Section: Pericardial Effusion and Constrictiv Pericarditismentioning
confidence: 99%
“…Table 1 summarizes key study characteristics. Topically, 20 studies pertained to liver transplant, [27][28][29][30][31][32][33][34][35][36][52][53][54][55][56][57][58][59]77,78 15 to lung transplant, 5, [38][39][40][41][64][65][66][67]69,71,72,[74][75][76] 9 to kidney transplant, 25,26,[46][47][48][49][50][51]73 6 to heart transplant, [22][23][24][43][44][45] 1 to small bowel transplant, 68 2 to pancreas-kidney tr...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In heart transplant, 2 studies evaluated risk factors specific to IA. 22,24 Renal replacement therapy (OR, 3.44; CI, 1.68-7.04) 22,24 increased the risk of early post-heart transplant IA with moderate certainty of evidence.…”
Section: Heart Transplantmentioning
confidence: 99%
See 1 more Smart Citation